Implementasi Range of Motion Pasif terhadap Percepatan Bromage Score Pasien Pasca Anestesi Spinal di Rumah Sakit Khusus Bedah Jatiwinangun Purwokerto - Ikhlas Mapolawa; Wilis Sukmaningtyas; Feti Kumala Dewi (Nusantara: Jurnal Pengabdian kepada Masyarakat, 2026)
Delayed recovery of motor function following spinal anesthesia may prolong recovery room stay and delay early mobilization. Passive Range of Motion (ROM) is a simple non-pharmacological intervention that may accelerate motor recovery. To describe the implementation of passive ROM in accelerating Bromage Score recovery among patients after spinal anesthesia at Rumah Sakit Khusus Bedah Jatiwinangun Purwokerto. This community service program involved 30 postoperative spinal anesthesia patients who met the inclusion criteria. Activities included patient education, assessment of Bromage Score before intervention, passive ROM implementation for 5–10 minutes, and post-intervention evaluation. Data were analyzed descriptively using frequency distribution. Most participants were 17–45 years old (76.7%), male (60%), classified as ASA I (66.7%), received 10 mg hyperbaric bupivacaine (46.6%), and had no previous surgical history (66.7%). Before intervention, all participants had Bromage Score 3 (100%). Following passive ROM, 60% achieved Bromage Score 1, with an average recovery time of 41 minutes. Passive ROM is a practical, safe, and feasible intervention that may accelerate motor recovery after spinal anesthesia and support early postoperative mobilization.